2022
DOI: 10.1186/s13568-022-01437-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiological characteristics of carbapenem-resistant Klebsiella pneumoniae among children in China

Abstract: Klebsiella pneumoniae infection and antimicrobial resistance among children are major concerns. The occurrence of hypervirulent K. pneumoniae (hvKp) infections is gradually increasing worldwide, and disinfectant resistance is also being reported. Carbapenem- and disinfectant-resistant hvKp infection has made clinical treatment and nosocomial infection control among children increasingly challenging. In this study, whole-genome sequencing was conducted among 34 Carba NP-positive carbapenem-resistant K. pneumoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…In China, it has been reported that the presence of KPC is responsible for carbapenem resistance in adult and pediatric isolates. 25 , 42 The present work demonstrated that the NDM and KPC genes detected in CRKP were mainly isolated in children and adults, respectively. Although OXA-48 is a prevalent carbapenemase type associated with Kp in some European countries, such as France and Turkey, 43 , 44 it is seldom detected in Kp isolates in China, 45 , 46 and the present study further support the observation that OXA-48 is not currently the primary carbapenemase types associated with Kp in China.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In China, it has been reported that the presence of KPC is responsible for carbapenem resistance in adult and pediatric isolates. 25 , 42 The present work demonstrated that the NDM and KPC genes detected in CRKP were mainly isolated in children and adults, respectively. Although OXA-48 is a prevalent carbapenemase type associated with Kp in some European countries, such as France and Turkey, 43 , 44 it is seldom detected in Kp isolates in China, 45 , 46 and the present study further support the observation that OXA-48 is not currently the primary carbapenemase types associated with Kp in China.…”
Section: Discussionsupporting
confidence: 55%
“… 51 In Jiangsu Province, and Wuhan, China, the main antimicrobial resistance gene in pediatric patients carried by CRKP was KPC2, and the prevalent strains were ST11 with high virulence and antimicrobial resistance. 6 , 25 Another work in Shenzhen demonstrated that ST307 was the most dominant genotype, and NDM represented the main resistance mechanism. 52 On the other hand, most of the isolates belonged to ST2407, which produces NDM enzymes, as revealed in this work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 The most common mechanism of carbapenem resistance in K. pneumoniae collected from children is KPC-2, but the prevalence of NDM, especially NDM-1, is higher than in adults in China. 10 , 11 The dominant clone of CRKP is ST11, which usually carries multiple resistance genes via plasmids and causes nosocomial infection outbreaks. 12 The spread of ST11 may have contributed to the increasing trend of multiple and even extensive drug resistance in K. pneumoniae since 2015.…”
Section: Amr Prevalence and Trends In Gram-negative Bacillimentioning
confidence: 99%
“…With the widespread use of carbapenem antibiotics, there have been an increasing number of corresponding carbapenem-resistant Enterobacterales (CRE). 1 The World Health Organization (WHO) and the Centers for Disease Control and Prevention (CDC) emphasize that CRE is an urgent threat to public health. 2 Klebsiella pneumoniae , one of the most significant species of Enterobacterales , is second only to Escherichia coli in the clinical isolation rate among gram-negative bacilli.…”
Section: Introductionmentioning
confidence: 99%